Search for decays of the Higgs boson into a pair of pseudoscalar particles decaying into Formula Presented using Formula Presented collisions at Formula Presented with the ATLAS detector - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Astrand, K.S.V.; Doglioni, C.; Ekman, P.A. ; 0000-0002-7032-2799; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Simpson, N.D.; Smirnova, O. ; 0000-0003-2517-531X; et al. (Physical Review D, 2024)
This paper presents a search for exotic decays of the Higgs boson into a pair of new pseudoscalar particles, Formula Presented, where one pseudoscalar decays into a Formula Presented-quark pair and the other decays into a Formula Presented-lepton pair, in the mass range Formula Presented. The analysis uses Formula Presented collision data at Formula Presented collected with the ATLAS detector at the LHC, corresponding to an integrated luminosity of Formula Presented. No significant excess above the Standard Model (SM) prediction is observed. Assuming the SM Higgs boson production cross section, the search sets upper limits at 95% confidence level on the branching ratio of Higgs bosons decaying into Formula Presented, Formula Presented), between 2.2% and 3.9% depending on the pseudoscalar mass. © 2024 CERN, for the ATLAS Collaboration.